Impact of large-scale photovoltaic-energy storage power generation system access on differential protection of main transformer under symmetrical faults - Yang, Guosheng; Zhang, Jiaqi; Zhang, Hao; Wang, Congbo; Zhu, Yujia; Chen, Xiaolong (Frontiers in Energy Research, 2023)
The low voltage ride-through (LVRT) requirements demand large-scale photovoltaic (PV) power generation system remain connected to the grid during faults. It results in considerable impact on the characteristics of fault current. This paper combines charge-discharge characteristics of the energy storage (ES) with PV generation system to enhance the LVRT capability. Based on the inverter control strategy and specific LVRT requirements, fault current characteristics of the PV-ES power generation system is discussed in this paper. In order to analyze the fault characteristic, the fault current expression as three-phase short-circuit faults occurs on both sides of the main transformer is calculated. Furthermore, taking the winding connection of the transformer into account, the ratio of differential current to braking current is further derived to find out the factors influencing the performance of the transformer differential protection. It is found that factors influencing the transformer differential protection include the rated capacity of the PV-ES generation system, fault severity, the length of transmission line and so on. And as the rated capacity of the PV-ES power generation system increase, the transformer differential protection would experience reduced sensitivity or even do not trip. The findings of this paper can lay a foundation for further improvement of the transformer differential protection. The elaborate performance evaluation of transformer differential protection, including the operation condition of the second harmonic braking element, is presented and verified by simulation using MATLAB/Simulink.